Amiodarone-induced myxoedema coma. (12th April 2014) - Hassan, Syed; Ayoub, Walaa; Hassan, Mona; Wisgerhof, Max
Abstract : A 62-year-old man was found to have bradycardia, hypothermia and respiratory failure 3 weeks after initiation of amiodarone therapy for atrial fibrillation. Thyroid-stimulating hormone was found to be 168 μIU/mL (nl. 0.3–5 μIU/mL) and free thyroxine (FT4) was <0.2 ng/dL (nl. 0.8–1.8 ng/dL). He received intravenous fluids, vasopressor therapy and stress dose steroids; he was intubated and admitted to the intensive care unit. He received 500 μg of intravenous levothyroxine in the first 18 h of therapy, and 150 µg intravenous daily thereafter. Haemodynamic improvement, along with complete recovery of mental status, occurred after 48 h. Twelve hours after the initiation of therapy, FT4 was 0.96 ng/dL. The patient was maintained on levothyroxine 175 (g POorally daily. A thyroid ultrasound showed diffuse heterogeneity. The 24 hour excretion of iodine was 3657 (mcg (25–756 ( mcg). The only two cases of amiodarone-induced myxoedema coma in the literature report patient death despite supportive therapy and thyroid hormone replacement. This case represents the most thoroughly investigated case of amiodarone-induced myxoedema coma with a history significant for subclinical thyroid disease.